From farm to table: Women at the agriculture-nutrition nexus - Quisumbing, Agnes R.; Kyle, Jordan; Kosec, Katrina; Ragasa, Catherine; Raghunathan, Kalyani; Kumar, Neha; Sawhey, Tinni; Gonzalez, Teresa; Madero, Ana; Mittrick, Caitlin; Myers, Emily; Rapada, Amica; et al. (International Food Policy Research Institute, 2025)
Presentation titles: Women in the Agriculture-Nutrition Pathways How Can Anticipatory Action Programming Support Women? Improving Women’s Livelihoods and Gender Equality through Women’s and Men’s Leadership and Advocacy Trainings in Rural Nigeria Role of Policy in Agriculture-Nutrition-Empowerment Nexus